2011
DOI: 10.1016/j.rehab.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Physical and rehabilitation medicine (PRM) care pathways: “Stroke patients”

Abstract: This document is part of a series of documents designed by the French Physical and Rehabilitation Medicine Society (SOFMER) and the French Federation of PRM (FEDMER). These documents describe the needs for a specific type of patients; PRM care objectives, human and material resources to be implemented, chronology as well as expected outcomes. "Care pathways in PRM" is a short document designed to enable the reader (physicians, decision-maker, administrator, lawyer or finance manager) to quickly apprehend the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…However, our approach was consistent with previous health economic studies on stroke and/or thrombolysis in France and in the international literature. Indeed, the post-acute clinical pathways were defined based on the Ministry of Health's guidelines [6] and Fery-Lemonnier [8] report as well as on Yelnik et al [7]. French studies such as Launois et al [3] and Chevreul et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our approach was consistent with previous health economic studies on stroke and/or thrombolysis in France and in the international literature. Indeed, the post-acute clinical pathways were defined based on the Ministry of Health's guidelines [6] and Fery-Lemonnier [8] report as well as on Yelnik et al [7]. French studies such as Launois et al [3] and Chevreul et al .…”
Section: Discussionmentioning
confidence: 99%
“…The post-acute phase corresponds to the period following discharge and up until 1 year. Five post-acute clinical care pathways were defined, using the Ministry of Health guidelines [6] and recommendations from the French Physical and Rehabilitative Medicine Society (SOFMER) and the French Federation of Physical and Rehabilitative Medicine (FEDMER) (hereafter referred to as Yelnik et al [7]). The post-acute phase pathways were the following (fig.…”
Section: Methodsmentioning
confidence: 99%
“…The main coordination problems encountered after patient discharge from hospital were poor information transfer from hospital to downstream staff, on the one hand, and delays due to administrative procedures, on the other [51]. Solutions to such problems might be holistic initiatives such as, for instance, integrated PRM care pathways [6,52] and early supported discharge procedures which have been shown to reduce long-term dependency, admissions to institutional care facilities, and length of hospital stay, at least in a selected elderly group of stroke patients with moderate disability [53]. In summary, for a SCP to function well, health professionals need to collaborate closely.…”
Section: Discussionmentioning
confidence: 99%
“…14 In France, after initial care in a stroke unit (approximately 10 days), the patient may be discharged directly home or he or she may be sent for rehabilitation, which, in France, may be carried out in a neurological rehabilitation center (NRC) with specialized, coordinated rehabilitation or in a general or geriatric rehabilitation center (GRC). 15 In a previous study, we showed that in France, the vast majority of patients admitted for rehabilitation went to GRC. 16,17 Older patients with a severe initial impairment and those with cognitive impairments tend to be more frequently admitted to GRC.…”
Section: Introductionmentioning
confidence: 93%